PORTOFOLIO OPTIMAL INDEKS LQ 45 METODE INDEKS TUNGGAL - Bonnie Mindosa; Bernadetta Dwi Suatmi; Jeffrey Van Halen (Jurnal Manajemen, 2021)
This study aims to develop an optimal stock portfolio using the single index method on the stocks listed on the LQ 45 Index in the 2018 – 2020 period. This study also aims to calculate the proportion of funds in each stock, the return and risk of the portfolio optimally formed. The single index method is a simplification of the Markowitz model. Based on the observation that the price of a security fluctuates in the direction of the market price index so that the single index method does not require much variance and covariance in calculating risk. The data in this study are secondary data obtained from Yahoo Finance, OJK, and IDX. The number of samples taken amounted to 29 companies using purposive sampling method. The analytical technique used is descriptive analysis with data processing using Microsoft Excel. The results of this study indicate the optimal portfolio combination containing 3 stocks with the proportion of each share, namely: ANTM (Aneka Tambang Tbk.) of 61.20%, INCO (Vale Indonesia Tbk.) of 18.15%, and BBCA (Bank Central Asia Tbk.) by 20.65%. The optimal portfolio formed has a return rate of 0.1397% with a risk level borne by investors of 0.07%. Next research is expected to use a longer research period and also can use other optimal portfolio methods. Keywords: Optimal Stock Portfolio, single index method, Return, Risk.